Long-term care hospitals as end-of-life care settings in South Korea: A nationwide analysis of utilization patterns and clinical trajectories - Haein Kim; Seungwon Shin (PLoS ONE, 2026)
Objectives This study aimed to investigate the utilization patterns and end-of-life trajectories of older adults in Korean long-term care hospitals (LTCHs) using nationwide population-based data. Methods This retrospective observational study analyzed National Health Insurance Service claims data (2014–2023). We constructed three analytical groups: an annual inpatient group to examine longitudinal trends in volume and mortality; a newly admitted inpatient group to assess the sociodemographic profile at the time of LTCH entry; and a decedent group to reconstruct the clinical trajectory and cumulative resource use from initial admission to death. Results While the volume of older inpatients increased, the annual number of deaths involving LTCH use increased from 68,357 in 2014 to 112,157 in 2023 over the decade. Patients were newly admitted to LTCHs in their early 80s (median age 81 years, IQR 75–86) and were predominantly female (62.1%). In addition, Medical Aid beneficiaries (13.7%) and individuals with registered disabilities (28.0%) were overrepresented, indicating high sociodemographic vulnerability. Decedents spent a median of 79 days (IQR 22–299) as LTCH inpatients. While 30.1% stayed for <30 days, 22.2% remained hospitalized for ≥ 360 days, indicating substantial variation in length of stay. Overall, 68.5% of decedents died during LTCH stay. While admissions were driven by chronic geriatric syndromes, the end-of-life phase was dominated by a surge in acute infectious and systemic conditions (e.g., pneumonia, 10.2% to 22.3%; sepsis, 3.3% to 11.9%). Conclusions LTCHs in Korea have played an increasingly important role as a setting for end-of-life care, managing a distinct trajectory from chronic frailty to acute deterioration. Given that these institutions are functioning as end-of-life care settings, policy reforms should strengthen palliative care integration, advance care planning, workforce training, and end-of-life care capacity within LTCHs.